The big book of makerspace projects : inspiring makers to experiment, create, and learn - Graves, Colleen (McGraw Hill Education, 2017)
Provides an interactive, easy-to-follow guide that is filled with classroom-tested, low-cost DIY makerspace projects and challenges that feature clear, non-technical step-by-step instructions inspire creativity and foster imagination in makers at every skill level. Features dozens of classroom-tested, hands-on DIY projects and challenges. Each project features clear, non-technical step-by-step instructions with photos and illustrations to ensure success, expand the imagination, and foster innovation. You will explore recyclables hacks, smartphone tweaks, paper and sewing circuits, e-textiles, musical instruments, coding and programming, and 3-D printing.